Lifelong physical activity - Baricevic, Thomas; LcLean, Matt.; De Robbio, Micheal (Australia : VEA, 2012)
Looks at the benefits of regular physical activity from a young age. Discusses the physical, mental and social outcomes of physical activity, exploring the positive and negative aspects of group and individual activities, including barriers to participation and how people from different backgrounds can overcome these challenges.
Director, Thomas Baricevic; writer, Matt McLean; producer, Michael De Robbio.
Voice-over, Nathan Derrick.
Keywords: Physical fitness; Exercise